E-056 Safety and effectiveness of preoperative endovascular vertebral artery sacrifice. (23rd July 2017) - Wallace,; Austin, M; Kamran, M; Kansagra, A; Osbun, J; Cross, D; Moran, C
Abstract : Background and Purpose: Endovascular vertebral artery sacrifice is performed to facilitate surgical resection of cervical spine tumors that encase or are in close proximity the vertebral artery, other surgeries that necessitate vertebral artery transection active extravasation or delayed pseudoaneurysm secondary to penetrating trauma or deceleration injury. Herein, we report our experience with this procedure. Materials and Methods: Institutional review board approval was obtained to retrospectively review the neurointerventional databases of a tertiary medical center for all cases of endovascular vertebral artery sacrifice performed between January 2003 and December 2016. Demographic information, clinical history, and outcomes were collected from electronic medical records. Procedural details and periprocedural complications were collected from operative reports. Preoperative digital subtraction angiography (DSA) was reviewed for details of vertebral artery anatomy. Results: During the study period, 15 unilateral endovascular vertebral artery occlusions were performed. The cohort included 10 men and 5 women with a mean age of 55 years (range, 18–82 years). Indications for the procedure included preoperative vertebral artery sacrifice prior to cervical tumor resection (80%; 12/15), surgical fixation of a C4-C5 fracture subluxation associated with an occlusive vertebral artery dissection, surgical removal of a misplaced central line, and delayed pseudoaneurysm after gunshot trauma. The vertebral arteries were codominant in 73% (11/15) of cases. The non-dominant vertebral artery was occluded in 20% (3/15) of cases. The dominant vertebral artery was occluded in one case in which the contralateral vertebral artery measured 3 mm in maximum diameter. Prior to endovascular occlusion, the vertebral arteries were patent and normal caliber (47%; 7/15), patent but narrowed (47%; 7/15), and occluded in 1 case. Successful endovascular occlusion was achieved in 93% (13/14) of cases performed prior to surgical transection of the target artery. The mean diameter of the occluded vertebral artery segment was 3.3 mm (range, 1.7–5.7 mm). The vertebral arteries were most commonly occluded using coils (53%; 8/15) or a combination of coils and Micro Vascular Plugs (33%; 5/15; Medtronic; Plymouth, MN). One vertebral artery was occluded with a combination of coils and an Amplatzer Vascular Plug (Medtronic; Plymouth, MN) and 42 coils (patient 11), and one was occluded with 5 Micro Vascular Plugs (patient 13). The mean numbers of coils used without and with vascular plugs were 23 (range, 6–33) and 9 (range, 4–13), respectively. The mean number of Micro Vascular Plugs used in combination with coils was 2.9 (range, 1–5). Antecedent temporary balloon occlusion testing to confirm filling of the basilar artery and ipsilateral posterior inferior cerebellar artery from the contralateral vertebral artery was performed in four cases using a 7 × 7 mm (3 cases) or 4 × 7 mm (1 case) HyperForm balloon. In each of these cases the balloon was also used to arrest antegrade flow during occlusion. Five patients (33%; 5/15) received aspirin postoperatively. There were no procedure-related complications. Conclusion: Endovascular vertebral artery sacrifice is a safe and effective treatment for minimizing blood loss during surgeries that involve transection of the vertebral artery. Disclosures: A. Wallace: None. M. Austin: None. M. Kamran: None. A. Kansagra: None. J. Osbun: None. D. Cross: None. C. Moran: 2; C; Medtronic Neurovascular, Microvention.